Long-Term Persistence of Olfactory and Gustatory Disorders in COVID-19 Patients - Nguyen, Nhu Ngoc; Hoang, Van Thuan; Dao, Thi Loi; Meddeb, Line; Cortaredona, Sébastien; Lagier, Jean-Christophe; Million, Matthieu; Raoult, Didier; Gautret, Philippe (Frontiers in Medicine, 2022)
Smell and taste disorders are frequent symptoms during acute COVID-19 and may persist long after the resolution of the initial phase. This study aims to estimate the proportion and risk factors for smell and/or taste disorders at the onset of symptoms and their persistence after more than six months of follow-up in COVID-19 patients. We analysed a prospective cohort of COVID-19 patients admitted to our institute in Marseille, France in early 2020. After being discharged from the hospital, patients with smell and/or taste disorders were contacted for a telephone interview. Logistic regression analysis was performed to determine the risk factors for smell and/or taste disorders. A total of 3,737 patients were included, of whom 1,676 reported smell and/or taste disorders at the onset of symptoms. Taste and/or smell disorders were independently associated with being younger and female, a lower likelihood of suffering from diabetes, cardiovascular diseases and cancer, a longer delay between the onset of symptoms and consultation, and non-severe forms of COVID-19 at admission. Of the 605 patients with smell and/or taste disorders who were followed-up, 154 (25.5%) reported the persistence of symptoms for more than six months. At the time of follow-up, being female, having a chronic respiratory disease and using angiotensin-converting enzyme inhibitors (ACEis) were factors independently associated with the persistence of smell and/or taste disorders. In conclusion, the long-term persistence of olfactory and gustative disorders is frequent among COVID-19 patients, notably affecting female patients and patients who suffered from chronic respiratory diseases before infection. The role of ACEis needs to be further evaluated in larger numbers of patients.